The Problem of Classification of Targets in Informational Conflicts - S. V. Korostelev (Управленческое консультирование)
As a result of changes in the technological tenor and congruous with it organization of the world economy, serious changes have occurred in the gradation of participants in armed conflicts. Firstly, the warring parties are not only states now. Secondly, the vast majority of the targets to be overpowered to ensure victory in the conflict are currently in the private sector and out of state control. Also, an essential feature of the information confrontation is that in the vast majority of situations, the direct perpetrator of an information attack cannot be identified immediately and to a large extent due to the fact that “military” conflicts in cyberspace in the context of international relations can be “embedded” in various forms of struggle for power: political, economic, informational, technological, media and ideological, etc. That is, a significant number of participants in ordinary everyday life implicit activities in all walks of life from all over the globe can be not only indirect but also direct participants of informational conflict.In the digital era, targets selected for destruction can have completely different and unexpected properties, which leads to the existence of a significant number of approaches to the classification of targets of informational impact. Force is used against physical and virtual objects in the physical, informational and cognitive dimensions.The complexity of assessing the physical damage inflicted on states, and their population in the cognitive sphere conformably, and relating it with the practice of assigning international responsibility for the use of traditional means of warfare makes it impossible to form any adequate universal international political and legal regime for countering information threats in the near future. The elimination of threats in cyberspace is a common interest in ensuring international stability, but at present it can be carried out by states only on their own.A statement of the specified list of unacceptable aggressive actions carried out through information influences in the federal legislation will be, in essence, a preventive measure, since it will establish a threshold restriction for other international actors to interfere in the internal affairs of the state from outside.